Features of experimental strain determination ofcompressed-bent elements considering their deflection curve - Krayinskyi, P. I.; Blikharskyi, Ya. Z.; Khmil, R. Ye. (Видавництво Львівської політехніки, 2014)
The method of experimental measurement of deformation of the upper fiber concrete reinforcement to bringing them further for real values of deformation. Наведено методику експериментального вимірювання деформації верхньої фібри бетону, арматури з приведенням їх надалі для отримання реальних величин деформації.
Keywords: research; concrete structures; дослідження; залізобетонні конструкції